Expression analysis of phosphate induced genes in contrasting maize genotypes for phosphorus use efficiency - Vasconcelos,M. J. V. (2022)
Abstract Phosphorus is an essential nutrient for plant growth and development. The ability of plants to acquire phosphate (Pi) from the rhizosphere soil is critical in the Brazilian Cerrado characterized by acidic soil. The induction of Pi transporters is one of the earliest molecular responses to Pi deficiency in plants. In this study, we characterize the transcriptional regulation of six (ZmPT1 to ZmPT6) high-affinity Pi transporters genes in four Pi-efficient and four Pi-inefficient maize (Zea mays) genotypes. The expression analysis indicated that Pi-starvation induced the transcription of all ZmPT genes tested. The abundance of transcripts was inversely related to Pi concentration in nutrient solution and was observed as early as five days following the Pi deprivation. The Pi-starved plants replenished with 250 µM Pi for four to five days resulted in ZmPT suppression, indicating the Pi role in gene expression. The tissue-specific expression analysis revealed the abundance of ZmPT transcripts in roots and shoots. The six maize Pi transporters were primarily detected in the upper and middle root portions and barely expressed in root tips. The expression profiles of the six ZmPTs phosphate transporters between and among Pi-efficient and Pi-inefficient genotypes showed an absence of significant differences in the expression pattern of the ZmPTs among Pi-efficient and Pi-inefficient genotypes. The results suggested that Pi acquisition efficiency is a complex trait determined by quantitative loci in maize.